Shelf Life and Simulated Gastrointestinal Tract Survival of Selected Commercial Probiotics During a Simulated Round-Trip Journey to Mars - Fajardo-Cavazos, Patricia; Nicholson, Wayne L. (Frontiers in Microbiology, 2021)
To enhance the gastrointestinal health of astronauts, probiotic microorganisms are being considered for inclusion on long-duration human missions to the Moon and Mars. Here we tested three commercial probiotics–Bifidobacterium longum strain BB536, Lactobacillus acidophilus strain DDS-1, and spores of Bacillus subtilis strain HU58–for their survival to some of the conditions expected to be encountered during a 3-year, round trip voyage to Mars. All probiotics were supplied as freeze-dried cells in capsules at a titer of >10^9 colony forming units per capsule. Parameters tested were survival to: (i) long-term storage at ambient conditions, (ii) simulated Galactic Cosmic Radiation and Solar Particle Event radiation provided by the NASA Space Radiation Laboratory, (iii) exposure to simulated gastric fluid, and (iv) exposure to simulated intestinal fluid. We found that radiation exposure produced minimal effects on the probiotic strains. However, we found that that the shelf-lives of the three strains, and their survival during passage through simulations of the upper GI tract, differed dramatically. We observed that only spores of B. subtilis were capable of surviving all conditions and maintaining a titer of >10^9 spores per capsule. The results indicate that probiotics consisting of bacterial spores could be a viable option for long-duration human space travel.